Developing of Metal-Halide Perovskite-Type Materials for electrodes of Lithium-Ion Batteries (2023)
ABSTRACT : Hybrid and inorganic metal halides with perovskite-type structures have been successfully applied in the battery field thanks to their 3D diffusion channels and robust architecture, which allow relatively high charge mobility, leading to easy metal-ion intercalation, as well as tunable electrical properties of the structure due to atom substitutions. The present work was focused to explore alternative active material of ABX3- perovskite type of metal-halide as an electrode with the use of components, such as fluorides, chlorides, sodium salts, and transition metals as nickel, iron, and manganese that are earth-abundant material, with accurate geographical distribution, less cost, and more environmentally friendly than other elements as lead and cobalt. Those electrodes were explored from easier routes of synthesis such as solvothermal, milling, and evaporation process which would expect to reduce the cost of battery production. All of that makes it an attractive material electrode for exploration mainly in lithium-ion batteries, however some evaluations were carried out also in sodium-ion batteries. The study began with ternary materials from NaCl-FeCl2 system evaluation. In this case discarded NaFeCl3 formation, however, alternative ternary as Na2Fe3Cl8 was studied. To obtain the ABX3 perovskite type structure the Cl element was substituted by F atom for what NaMnF3 and NaNiF3 perovskite structures were explored. In those cases, different morphologies and sizes of particles were studied by microwave and conventional heating, with the incorporation of carbonaceous components that interact with the active material creating a continuous conductive phase control that could improve some electrochemical performances. Additionally, a composite NaNiF3/Ni was obtained by electrochemical dissolution of nickel foam. These materials were evaluated as an electrode in lithium and sodium-ion semi-cells. Finally, a hybrid organic-inorganic CH3NH3NiCl3 active material was studied as an electrode in lithium-ion cells by conventional and electrochemical reversibility processes. That material conserved the chemistry composition of ABX3-type where X is Cl. Although this structure is deflected from perovskite structure its stability was conserved by replacing the Na+ inorganic by CH3NH3+ organic cation. The mechanism of reaction in those active material electrodes with ABX3 perovskite-type structures was also studied, and here was confirmed a conversion-type mechanism in the case of the inorganic materials, while for the hybrid material, it may drive a combination of reaction mechanisms such as intercalation, conversion, and alloying.